2010
DOI: 10.1080/17470210903004638
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of spatial Stroop by object-based attention but not by space-based attention

Abstract: Earlier studies have shown that the spatial Stroop effect systematically decreases when a peripheral precue is presented at the same location as the target, compared to an uncued location condition. In this study, two experiments were conducted to explore whether the cueing modulation of spatial Stroop is object based and/or space based. In Experiment 1, we found evidence favouring the view that the cueing modulation of the spatial Stroop effect is entirely object based, as no differences were found in conflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Similar results have been observed in other studies (Brown & Denney, 2007;Lamy & Egeth, 2002;Lamy & Tsal, 2000;Luo, Lupiáñez, Funes & Fu, 2010, 2011Vecera, 1994).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Similar results have been observed in other studies (Brown & Denney, 2007;Lamy & Egeth, 2002;Lamy & Tsal, 2000;Luo, Lupiáñez, Funes & Fu, 2010, 2011Vecera, 1994).…”
supporting
confidence: 81%
“…An attentional spreading view of object-based attention proposes that attentional spreading through an attended object can improve the rate and efficiency of perceptual processes, which likely enhances the representation of the attended object relative to unattended objects (Cosman & Vecera, 2012;Desimone & Duncan, 1995;Luo et al, 2010Luo et al, , 2011. This view can explain the object-based effects observed in the two-rectangle cueing paradigms (Egly et al, 1994;Lamy & Tsal, 2000;Vecera, 1994) by proposing that targets displayed in an attended object are more likely to be attended because attention spreads readily within objects but not across objects.…”
mentioning
confidence: 89%
“…In this case, location information from the cue can be used to localize the target, leading to improved target processing (Funes et al, 2005). The spatial match may also be flexibly adjusted to the structure of the entire visual field: Since "spatial Stroop," usually reduced by spatial cues, is reduced not only at the cued location, but also for the entire cued object (Luo, Lupiáñez, Funes, & Fu, 2010), it was suggested that all locations of an object can be integrated into one event. In this regard, the texture advantage found in the present series of experiments could be explained in terms of a spatial match assumption.…”
Section: Texture Advantage As a Results Of Event Integration Processesmentioning
confidence: 99%
“…Actually, we have recently observed some evidence indicating that the modulation of cueing on spatial interference is object based, as predicted by the event integration account (Luo, Lupiáñez, Funes, & Fu, 2009;Experiment 1). In this study, we combined a double-rectangle cueing task developed by Egly, Driver and Rafal (1994) with the spatial Stroop task used by Lupiáñez and Funes (2005) to separate the role of object-based and space-based attention on spatial codes and to further understand the role of attention in the generation and modulation of spatial codes.…”
Section: Discussionmentioning
confidence: 92%